2013
DOI: 10.1093/hmg/ddt449
|View full text |Cite
|
Sign up to set email alerts
|

Identification of FHL1 as a therapeutic target for Duchenne muscular dystrophy

Abstract: Utrophin is a potential therapeutic target for the fatal muscle disease, Duchenne muscular dystrophy (DMD). In adult skeletal muscle, utrophin is restricted to the neuromuscular and myotendinous junctions and can compensate for dystrophin loss in mdx mice, a mouse model of DMD, but requires sarcolemmal localization. NFATc1-mediated transcription regulates utrophin expression and the LIM protein, FHL1 which promotes muscle hypertrophy, is a transcriptional activator of NFATc1. By generating mdx/FHL1-transgenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Dysregulation of FHL1 due to mutations in this protein are causative for several forms of human X-linked skeletal muscle dystrophies: Emery-Dreifuss muscular dystrophy, reducing body myopathy, rigid spine syndrome, scapuloperoneal myopathy, and X-linked myopathy with postural muscle atrophy [reviewed in (126)]. FHL1 upregulation is potentially therapeutic for skeletal myopathies as upregulation can rescue a DMD mouse model ( mdx model) by increasing muscle hypertrophy through the NFAT pathway (136). Furthermore, upregulation of FHL1 is detected at early stages of DCM progression in multiple mouse models, making it a promising candidate as a marker of early detection of DCM (195).…”
Section: Sarcomere—the Basic Contractile Unit Of Striated Musclementioning
confidence: 99%
“…Dysregulation of FHL1 due to mutations in this protein are causative for several forms of human X-linked skeletal muscle dystrophies: Emery-Dreifuss muscular dystrophy, reducing body myopathy, rigid spine syndrome, scapuloperoneal myopathy, and X-linked myopathy with postural muscle atrophy [reviewed in (126)]. FHL1 upregulation is potentially therapeutic for skeletal myopathies as upregulation can rescue a DMD mouse model ( mdx model) by increasing muscle hypertrophy through the NFAT pathway (136). Furthermore, upregulation of FHL1 is detected at early stages of DCM progression in multiple mouse models, making it a promising candidate as a marker of early detection of DCM (195).…”
Section: Sarcomere—the Basic Contractile Unit Of Striated Musclementioning
confidence: 99%
“…Furthermore, a systemic strategy designed to increase the endogenous utrophin level to treat all skeletal muscle (including the diaphragm) and heart, would not be anticipated to result in an immune response ( 25 ). To date, direct delivery of the protein ( 35 ) or stabilization of the protein or RNA ( 36 , 37 ), viral approaches ( 38 , 39 ), non-viral strategies such as recombinant biglycan ( 40 ) and oral compound administration designed to modulate the utrophin expression at the transcriptional level ( 41 , 42 ), showed that maintaining utrophin expression in mdx muscle fibres could decrease the progression of the disease and represents a promising therapeutic avenue for DMD.…”
Section: Introductionmentioning
confidence: 99%
“…The myosin isoform MHY7, which was induced by more than 10 fold by tadalafil treatment, is also implicated in cardiac hypertrophy. Other hypertrophic markers such as the transcript variant four of PGC‐1α (PGC‐1α‐4; Ruas et al, ), FHL‐1 D'Arcy et al, ) and IGF‐1 were found to be overexpressed in dystrophic muscles following tadalafil treatment (Fig. ).…”
Section: Resultsmentioning
confidence: 95%